Perinatal factors for antepartum hemorrhage in women with placenta accreta spectrum - Hu, Pengzhen; Ye, Shaoxin; Zhou, Shuguang; Guo, Xiaoling; Fan, Dazhi (Frontiers in Surgery, 2025)
IntroductionPlacenta accreta spectrum with antepartum hemorrhage is closely related to maternal and fetal morbidity and mortality. It is of utmost importance to predict the possibility of antepartum hemorrhage using perinatal factors before delivery in women with placenta accreta spectrum. The aim of this study is to identify the risk factors for antepartum hemorrhage in women with placenta accreta spectrum.MethodsThis retrospective cohort study evaluated pregnant women with placenta accreta spectrum. Multivariate logistic regression was used to identify the independent variables associated with antepartum hemorrhage and a nomogram was developed to predict the possibility of antepartum hemorrhage. An Excel form computer interface was constructed to use the prediction model.ResultsThis retrospective cohort study included 188 participants (74 with antepartum hemorrhage). According to multivariate logistic regression analysis, blood type O [odds ratio (OR) 2.277, confidence interval (CI) 1.220–4.250], history of miscarriage (2.178, 95% CI 1.114–4.261), and parity (1.701, 1.037–2.790) were independent risk factors for antepartum hemorrhage in women with placenta accreta spectrum.DiscussionThis results revealed that women with placenta accreta spectrum with blood type O, history of miscarriage, and multiparity may have a significant risk of experiencing antepartum hemorrhage.